2012
DOI: 10.1007/s00464-012-2329-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the clinical and inflammatory responses in exclusively NOTES transvaginal cholecystectomy versus laparoscopic routes: an experimental study in swine

Abstract: The entirely NOTES transvaginal cholecystectomy was feasible and safe. The surgical time was greater for the NOTES vaginal route. The inflammatory response was similar among the groups based on the levels of CRP and IFN-γ. However, the evolution of the inflammatory process seems to have been shorter in the vaginal NOTES group than in the laparotomy group as demonstrated by the difference between the peak and basal doses of IFN-γ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 98 publications
2
6
1
Order By: Relevance
“…In our study, however, measurable levels of IL-1 β and IL-6 were present only in 7.3% and 43.3% of samples, respectively. Nevertheless, this finding is consistent with those of others who reported undetectable IL-1 β or IL-6 serum levels in most or even all samples [ 11 , 30 , 31 ]. Either the sensitivity of our assay was not low enough to detect small amounts of cytokines or we did not evaluate our samples at an optimal time.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our study, however, measurable levels of IL-1 β and IL-6 were present only in 7.3% and 43.3% of samples, respectively. Nevertheless, this finding is consistent with those of others who reported undetectable IL-1 β or IL-6 serum levels in most or even all samples [ 11 , 30 , 31 ]. Either the sensitivity of our assay was not low enough to detect small amounts of cytokines or we did not evaluate our samples at an optimal time.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, we observed constant TNF- α levels in all groups. Similarly, others have seen no differences between NOTES and laparoscopy in TNF- α [ 28 31 ]. For unknown reasons, the serum TNF- α concentrations in the transcolonic group were significantly higher than in the 2 other groups.…”
Section: Discussionmentioning
confidence: 95%
“…These issues contributed to increase the operative time in the hybrid NOTES cases compared to the laparoscopic cases. This finding is consistent with previous research [2, 8, 10, 18, 19, 20, 21, 22]. For instance, our analysis indicates that the emergence of new substeps to setup the transvaginal access increased the surgical time suggesting the requirement of a specific training for general surgeons to improve their performance in this step.…”
Section: Discussionsupporting
confidence: 92%
“…Currently, this technique is not easy to perform [7]. It is more demanding for the surgeons compared to conventional techniques, as it is more difficult to control the pressure during insufflation, and more difficult to use the unfamiliar new tools [8, 9]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation